2016
DOI: 10.1002/2015wr018250
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary sediment delivery and rapid geomorphic response following the 2008–2009 eruption of Chaitén Volcano, Chile

Abstract: The 10 day explosive phase of the 2008–2009 eruption of Chaitén volcano, Chile, draped adjacent watersheds with a few cm to >1 m of tephra. Subsequent lava‐dome collapses generated pyroclastic flows that delivered additional sediment. During the waning phase of explosive activity, modest rainfall triggered an extraordinary sediment flush which swiftly aggraded multiple channels by many meters. Ten kilometer from the volcano, Chaitén River channel aggraded 7 m and the river avulsed through a coastal town. That … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 71 publications
1
67
0
Order By: Relevance
“…Based on our data and literature examples, we infer that rivers in 10 2 –10 3  km 2 watersheds can export sediment pulses of similar or larger magnitude than that of the Elwha River dam removals (~10 7 t) with similar efficiency (moving >10 km in <5 yr) if the sediment is noncohesive, if flows have sufficient transport power (aided in some cases by hydraulic smoothing during large sediment loads 7 ), and where the channel gradient is ~0.003 or steeper 15,41,42,44,45 ; the Elwha River gradient below the dam sites is 0.004–0.008. A sediment pulse may cause minimal downstream geomorphic impact and evacuate more rapidly («1 year) even along a channel with 0.003 slope if the sediment pulse contains dominantly silt and clay 43 .…”
Section: Disturbance Response and Return To “Equilibrium”mentioning
confidence: 88%
“…Based on our data and literature examples, we infer that rivers in 10 2 –10 3  km 2 watersheds can export sediment pulses of similar or larger magnitude than that of the Elwha River dam removals (~10 7 t) with similar efficiency (moving >10 km in <5 yr) if the sediment is noncohesive, if flows have sufficient transport power (aided in some cases by hydraulic smoothing during large sediment loads 7 ), and where the channel gradient is ~0.003 or steeper 15,41,42,44,45 ; the Elwha River gradient below the dam sites is 0.004–0.008. A sediment pulse may cause minimal downstream geomorphic impact and evacuate more rapidly («1 year) even along a channel with 0.003 slope if the sediment pulse contains dominantly silt and clay 43 .…”
Section: Disturbance Response and Return To “Equilibrium”mentioning
confidence: 88%
“…An active volcano has a natural slope where sediment supply is regulated by the frequency and magnitude of the explosive activity. After a main eruption, lahar frequency increases due to the immediate reworking of pyroclastic material (Manville et al, 2009), even in correspondence to low accumulated rains , until it progressively decreases in the following years, as observed at Volcán de Colima (Davila et al, 2007;Capra et al, 2010) and other volcanoes (Lavigne, 2004;Thouret et al, 2014;Major et al, 2016). These factors, along with the physical features of the flows (i.e., sediment load, depth, volume, discharge, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The role that the slope, the sediment availability, rainfall distribution and flow dynamics play, among other parameters, has been studied for a long time (e.g., Coe et al, 2008;Guthrie et al, 2010;Berger et al, 2011;Schürch et al, 2011;Abancó and Hürlimann, 2014;Theule et al, 2015), and has served to extrapolate these findings to volcanic conditions. Previous studies found that the highest erosion rates in river basins (10 5 -10 6 m 3 km −2 yr −1 ) correspond to active volcanoes under humid climate (Milliman and Syvitski, 1992;Walling and Webb, 1996;Major et al, 2000). As observed by Lavigne (2004), for these types of volcanoes, the efficiency of erosion is a consequence of rain-triggered lahars that develop during the rainy season; converting the estimation of sediment yield and erosion rate is a very difficult task to achieve (Lavigne, 2004;Procter et al, 2010;Pierson et al, 2011;Thouret et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The lahars were triggered by intense rainfall in the aftermath of the initial eruptive phase (Pierson et al, ). The subsequent reworking of volcaniclastic sediments buried river channels and floodplain forests beneath up to 8–11 m of volcanic debris in places, setting in motion a cascade of channel avulsions, bank erosion, and log jams (Major et al, ; Major & Lara, ; Pierson et al, ; Swanson et al, ; Ulloa, Iroumé, Picco, et al, ). The Blanco River avulsed across Chaitén Township, buried large parts of the town beneath of sediments (Figure ), and formed a posteruptive fan delta at the head of the fjord (Major et al, ).…”
Section: Eruption Of Chaitén Volcanomentioning
confidence: 99%